Extraction of PCR-ready DNA from Staphylococcus aureus bacteriophages using carboxyl functionalized magnetic nonporous microspheres - Kahánková, Jana; Spanová, Alena; Pantůcek, Roman; Horák, Daniel; Doskar, Jirí; Rittich, Bohuslav (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2009)
Magnetic microspheres P(HEMA-co-EDMA) were used for PCR-ready phage DNA isolation from lysogenic strains of Staphylococcus aureus, including two new clinical isolates. The conditions of phage particle lysis were optimized. The quality of eluted phage DNA was evaluated by PCR. It was demonstrated that PCR-ready phage DNA can be isolated from small volumes of phage lysates (150 microl) by magnetic microspheres. The reported method is very expeditious without using toxic compounds such as phenol or chloroform. It can be used for phage identification and phage gene detection.
Keywords: Staphylococcus aureus; mikrosféry; Magnetics; magnetismus; Microspheres; Polymerase Chain Reaction; polymerázová řetězová reakce; Genetic Techniques; Solid Phase Extraction; extrakce na pevné fázi; stafylokokové bakteriofágy; DNA, Viral; genetické techniky; DNA virů; Staphylococcus Phages